The role of the microbiome and the use of probiotics in gastrointestinal disorders in adults in the Asia‐Pacific region ‐ background and recommendations of a regional consensus meeting. Issue 1 (28th December 2017) - Ghoshal, Uday C; Gwee, Kok‐Ann; Holtmann, Gerald; Li, Yanmei; Park, Soo Jung; Simadibrata, Marcellus; Sugano, Kentaro; Wu, Kaichun; Quigley, Eamonn M M; Cohen, Henry
Abstract: The Asia‐Pacific region is diverse, with regard to ethnicity, culture, and economic development incorporating some of the world's least and most developed nations. Gastrointestinal diseases are common in the Asia‐Pacific region, and their prevalence, presentation, and management vary considerably within the region. There is growing evidence for an important role for the human gut microbiota in gastrointestinal health. As a consequence, geographic variations in the composition of the gut microbiota may contribute to variations in both the prevalence and response to therapy of specific diseases. Probiotics have been proposed as a valuable option in the prevention and treatment of a number of gastrointestinal illnesses, but the quality of available evidence to support their efficacy is variable. A meeting of international experts in adult and pediatric gastroenterology was held at the Sorbonne University, Paris, France, on April 11 and 12, 2016, to discuss current evidence supporting the use of probiotics in gastrointestinal disorders in the Asia‐Pacific region. This article provides an overview of the discussions held at this meeting and recommends the formation of an Asia‐Pacific Consortium on Gut Microbiota similar to those established in Europe and North America.